2008
DOI: 10.1089/jpm.2007.0137
|View full text |Cite
|
Sign up to set email alerts
|

The End-of-Life Hospital Setting in Patients with Glioblastoma

Abstract: Despite aggressive treatment, outcome of patients with glioblastoma is poor. Several distinct clinical problems arise in the terminal stage of this disease. The purpose of this study was to evaluate the end-of-life phase in a hospital setting in patients with glioblastoma. Twenty-nine consecutive patients with glioblastoma, who died in our department, were included in this analysis regarding symptoms, medication, diagnostics, and interventional procedures. The patients were comparable with respect to age, gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 18 publications
3
48
0
4
Order By: Relevance
“…As a consequence of difficulties with managing acute symptoms at home, particularly seizures, admission to a hospital may be inevitable, which corresponds with previous reports on HGG patients [35,36]. Apart from impacting health care budgets, transitions in the EOL phase might affect a patient's personal dignity [17,37].…”
Section: Discussionsupporting
confidence: 70%
“…As a consequence of difficulties with managing acute symptoms at home, particularly seizures, admission to a hospital may be inevitable, which corresponds with previous reports on HGG patients [35,36]. Apart from impacting health care budgets, transitions in the EOL phase might affect a patient's personal dignity [17,37].…”
Section: Discussionsupporting
confidence: 70%
“…As such, timely involvement of the patient in treatment decisions (including supportive measures ahead) is of paramount importance. Two systematic reviews of studies addressing the EOL phase, in high-grade gliomas, showed a high burden of symptoms, namely reduced consciousness (44-90%), dysphagia (10-85%), headache (36-62%), seizures (10-56%), focal neurological deficits (>50%), cognitive disturbances (>30%), confusion (15-51%), and poor communication ( 64-90%) (227,(231)(232)(233)(234)(235)(236).…”
Section: Supportive Carementioning
confidence: 99%
“…14,15 Recent papers have reported that BT patients at the end of life present a high incidence of distressing symptoms that may impact their quality of life during the process of dying. 16,17 In order to allow the patient to experience a peaceful death, specific palliative interventions are necessary to control pain, confusion, agitation, delirium, or seizures. 18 In the large population of BT patients assisted until death by our neuro-oncological palliative home-care team since 2000, we have observed a high incidence of distressing symptoms impacting their quality of life during the last stage of disease and the process of dying.…”
Section: End Of Life Issues/treatment Decisionsmentioning
confidence: 99%
“…20 The majority of patients in their last month of life had difficulty taking oral medications due to dysphagia, disturbances in consciousness or both, which makes the use of the more commonly utilized oral antiepileptic drugs problematic at the end of life. 16,17 Thus, the anticonvulsant treatment in this stage of disease needs to be optimized, and oral treatment has to be adapted to find the optimal route for administering the drugs (intramuscular, rectal, transdermal, or subcutaneous).…”
Section: Seizuresmentioning
confidence: 99%